The Relationship Between Creative Mathematical Self Efficacy and Problem Solving Ability on FPB and KPK Material among Elementary Teacher Education Students - Mar’atu Zahra; Rina Dyah Rahmawati (Universitas Pendidikan Ganesha, 2026)
Problem solving ability is an essential skill in mathematics learning that is influenced by both cognitive and affective aspects. One affective factor that plays a role is Creative Mathematical Self Efficacy (CMSE), which refers to an individual’s belief in their ability to think creatively when solving mathematical problems. This study aims to analyze the relationship between CMSE and mathematical problem solving ability and to explore the contribution of CMSE to students’ mathematical performance. The study employed a quantitative approach with an ex-post facto correlational design involving 23 students in an elementary school teacher education program. Data were collected through a CMSE questionnaire and a problem solving test on the topics of Greatest Common Divisor (GCD) and Least Common Multiple (LCM). Data analysis was conducted using the Spearman and chi square tests because the data were not normally distributed. The results showed that CMSE had a very weak relationship, namely 18%, with mathematical problem solving ability. These findings indicate that problem-solving ability is not only influenced by CMSE, but also by other factors such as prior knowledge, learning strategies, and instructional approaches. The conclusion of this study indicates that CMSE functions as a supporting factor rather than the main determinant of students’ mathematical problem-solving ability. The implication of this study emphasizes the importance of designing mathematics learning holistically by integrating the strengthening of cognitive aspects, self-confidence, creativity, and students’ engagement in solving contextual problems.